The Relationship Between Sleep Quality and the Incidence of Hypertension in the Elderly in Koto Padang Village, the Working Area of the Koto Baru Dharmasraya Health Center in 2025 - costarin (Journal of health research and technology, 2026)
According to WHO (2018), every year it is estimated that around 20% - 50% of elderly people report poor sleep quality disorders and around 17% experience serious sleep disorders. The purpose of this study is to determine the relationship between sleep quality and the incidence of hypertension in the elderly. This study uses a spearman rank research design with a cross-sectional study approach. With a population of 198 elderly people. The sampling technique was accidental sampling, with a sample size of 35 people. This research was analyzed using univariate and bivariate analysis.Based on the results of the study, all elderly people, namely 35 people, experienced poor sleep quality and almost half, namely 17 people (48.6%) experienced mild hypertension. There was no significant correlation between sleep quality and the incidence of hypertension in the elderly in Koto Padang Village, the working area of the Koto Baru Community Health Center, Dharmasraya Regency with a p value of 0.324 which means greater than 0.05. The results of this study are expected to be a reference for community health centers and provide education to the elderly about the importance of quality sleep and ways to improve sleep quality, such as creating a healthy sleep routine, avoiding stimulants such as caffeine, and creating a comfortable sleeping environment.Keywords: Elderly, Sleep Quality, Hypertension